Immune Responses to Broad-Spectrum Antibiotic Treatment and Fecal Microbiota Transplantation in Mice - Ekmekciu, Ira; von Klitzing, Eliane; Fiebiger, Ulrike; Escher, Ulrike; Neumann, Christian; Bacher, Petra; Scheffold, Alexander; Kühl, Anja A.; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Immunology, 2017)
Compelling evidence demonstrates the pivotal role of the commensal intestinal microbiota in host physiology and the detrimental effects of its perturbations following antibiotic treatment. Aim of this study was to investigate the impact of antibiotics induced depletion and subsequent restoration of the intestinal microbiota composition on the murine mucosal and systemic immunity. To address this conventional C57BL/6j mice were subjected to broad-spectrum antibiotic treatment (ABx) for eight weeks. Restoration of the intestinal microbiota by peroral fecal microbiota transplantation (FMT) led to reestablishment of small intestinal CD4+, CD8+ and B220+ as well as of colonic CD4+ cell numbers as early as seven days post FMT. However, at d28 following FMT, colonic CD4+ and B220+ cell numbers were comparable to those in ABx mice. Remarkably, CD8+ cell numbers were reduced in the colon upon antibiotic treatment, and FMT was not sufficient to restore this immune cell subset. Furthermore, absence of gut microbial stimuli resulted in decreased percentages of memory/effector T cells, regulatory T cells and activated dendritic cells in the small intestine, colon, mesenteric lymph nodes (MLN) and spleen. Concurrent antibiotic treatment caused decreased cytokine production (IFN-γ, IL-17, IL-22, IL-10) of CD4+ cells in respective compartments. These effects were, however, completely restored upon FMT. In summary, broad-spectrum antibiotic treatment resulted in profound local (i.e. small and large intestinal), peripheral (i.e. MLN) and systemic (i.e. splenic) changes in the immune cell repertoire that could, at least in part, be restored upon FMT. Further studies need to unravel the distinct molecular mechanisms underlying microbiota-driven changes in immune homeostasis subsequently providing novel therapeutic or even preventive approaches in human immunopathologies.